Correlação da imunomarcação de α/βa-inibina e Minichromosome Maintenance Protein (MCM)-7 com diferenciação e prognóstico do carcinoma cervical escamoso - lara Veronica de Araújo Lopes (2023)
Cervical cancer (CC) is the fourth leading cause of cancer death in women. Therefore, the identification of cell differentiation and prognostic markers is extremely relevant for the treatment of the disease. Our hypothesis is that proteins involved in cell differentiation, activins and inhibins, and proliferation, minichromosome maintenance protein (MCM)-7, pathways would be associated with the development of more undifferentiated squamous cell carcinoma (SCC) phenotypes or with a worse prognosis, respectively. SCC specimens of moderately (MD-SCC; N=39) or poorly (PD- SCC; N=20) differentiated cervical tumors were recruited and submitted to immunohistochemical analysis for α-/ßA-inhibin subunits and MCM7. α- and βA-inhibin staining was detected both at the cytoplasmic and nuclear levels, more predominantly at the basal layer of the cervical epithelium. In MD-SCC, the area of cytoplasmic α-inhibin immunostaining was decreased in cells with a more undifferentiated phenotype (UP) compared to cells with a differentiated phenotype (DP cells) (p<0.01), whereas, DP nuclear α-inhibin staining was decreased in PD-SCC compared to MD-SCC (p<0.05). Cytoplasmic βA-inhibin intensity was decreased in UP compared to DP cells. By using a correlation matrix, we detected an evident decrease in the correlation coefficient of α-inhibin staining between the nuclei of DP, compared to UD cells in both MD- and PD-SCC tumors, whereas in PD-SCC tumors, an important loss of βA intensity correlation was detected between DP and UP cells. Morphometric analysis of MCM7 immunostaining detected its expression in the nucleus of tumor cells, both in MD-SCC and in PD-SCC. The mean immunostaining for MCM7 was 96%. Immunostaining percentages were compared with clinical and histopathological parameters associated with prognosis. No significant difference was observed in the % of tumor cell marking with the age of the patients and the degree of differentiation. However, there was a significant association between the higher percentage of MCM7 immunostained tumor cells and the depth of the lesion, the degree of tumor staging (FIGO), lymph node invasion, direct/distant metastasis and evolution to death in a period of less than 5 years ( p<0.05). Analysis of p16 immunostaining (high- risk HPV infection marker) revealed that 12% (7/58) of the samples were negative for HPV infection. There was evidence of a correlation trend of MCM7 higher immunostaining in tumor cells negative for p16, which was further associated with a worse prognosis. We conclude that α- /βA-inhibin subunits play an important role in the loss of cell differentiation in SCC and, consequently, in human cervical carcinogenesis, and that MCM7 has potential value as a prognostic biomarker for SCC. More studies are needed to expand knowledge on the role of α-/βA-inhibin in cervical carcinogenesis, and on the potential prognostic value of MCM7 in SCC